A interpessoalidade na comunicação via e-mail entre uma Coordenadora de Negócios Educacionais e seus colaboradores: um estudo sistêmico-funcional - Almeida, Anna Carolina Santos Martin [UNIFESP] (2019)
The objective of this research is to analyze the language used by an Educational Business Coordinator (EBC) on her e-mail exchanges with her co-workers, namely teachers, other EBCs and the principal of a vocational school. It starts out from the idea that language is the place of development of meaning and a fundamental resource in the development of the human experience (HALLIDAY, 1994). Research in the field of Applied Linguistics, such as Polifemi (2007) and Ninin (2009), report results about the role of the pedagogical coordinator, but due to intense technological and scientific changes and to new relationships established in the job market, part of the communication between the coordinator and her co-workers is carried out electronically, through technological digital means, in order to respond to the educational and market demands of private education institutions. Taking this scenario as a starting point, using the Systemic-Functional Grammar as theoretical framework proposed by Halliday and Matthiessen (2014), aiming to verify which linguistic choices are used by the EBC in her written interaction that characterize the social roles enacted and attributed by those who interact with her and verify the elements that allow to classify the e-mails that compose the corpus as a genre, as well as its organization in stages and its Genre Structure Potential, as proposed by Martin and Rose (2008). To reach this goal, the lexico-grammatical choices of 461 e-mails produced by the EBC in interaction with her co-workers that represent the interpersonal choices established and that compose the corpus focused in the following terms: folks, you, I, not, could, can, I am and we are, as well as the Schematic Structure (MARTIN, 1992, MARTIN; ROSE, 2008) of the e-mails will be analyzed. From the methodological point of view, we adopted qualitative research principles (FLICK, 2004), associated with SystemicFunctional Grammar principles (HALLIDAY, MATTHIESSEN, 2014) focusing on the interpersonal metafunction and in the context of culture (Genre), as well as in the variables of the context of situation (Register), such as proposed by Halliday and Hasan (1989) and Eggins (2004). As a computational tool, we used AntConc, based on Corpus Linguistics principles proposed by Berber-Sardinha (2004). Results show that (i) in the lexico-grammatical choices there is a movement between the administrative and the educational issues ranging between polarity and/or modality, whereas (ii) the analysis of the emails Schematic Structure reveal a prototypical model that allows us to characterize them as a discursive genre.